Biological sensitivities to high‐resolution climate change projections in the California current marine ecosystem. (28th July 2022) - Sunday, Jennifer M.; Howard, Evan; Siedlecki, Samantha; Pilcher, Darren J.; Deutsch, Curtis; MacCready, Parker; Newton, Jan; Klinger, Terrie
Abstract: The California Current Marine Ecosystem is a highly productive system that exhibits strong natural variability and vulnerability to anthropogenic climate trends. Relating projections of ocean change to biological sensitivities requires detailed synthesis of experimental results. Here, we combine measured biological sensitivities with high‐resolution climate projections of key variables (temperature, oxygen, and p CO2 ) to identify the direction, magnitude, and spatial distribution of organism‐scale vulnerabilities to multiple axes of projected ocean change. Among 12 selected species of cultural and economic importance, we find that all are sensitive to projected changes in ocean conditions through responses that affect individual performance or population processes. Response indices were largest in the northern region and inner shelf. While performance traits generally increased with projected changes, fitness traits generally decreased, indicating that concurrent stresses can lead to fitness loss. For two species, combining sensitivities to temperature and oxygen changes through the Metabolic Index shows how aerobic habitat availability could be compressed under future conditions. Our results suggest substantial and specific ecological susceptibility in the next 80 years, including potential regional loss of canopy‐forming kelp, changes in nearshore food webs caused by declining rates of survival among red urchins, Dungeness crab, and razor clams, and loss of aerobic habitat for anchovy and pink shrimp. We also highlight fillable gaps in knowledge, including specific physiological responses to stressors, variation in responses across life stages, and responses to multistressor combinations. These findings strengthen the case for filling information gaps with experiments focused on fitness‐related responses and those that can be used to parameterize integrative physiological models, and suggest that the CCME is susceptible to substantial changes to ecosystem structure and function within this century. Abstract : This work summarizes experimental results of biological responses to projected climate change in species of economic, cultural, and ecological importance along the US and Canadian west coast, and combines these with downscaled climate projections. While physiological rates generally increased with projected changes, fitness traits generally decreased, indicating that concurrent stresses can lead to fitness loss, and anticipated ecological change in the California Current Marine Ecosystem.